GANGGUAN CEMAS MENYELURUH: LAPORAN KASUS DAN TINJAUAN LITERATUR - Dian Budianti; Shinta Brisma; Dhina Lydia Lestari (Yayasan Nusantara Hasana Berdikari, 2025)
Generalized Anxiety Disorder (GAD) is a psychiatric condition characterized by excessive, persistent, and uncontrollable worry. It significantly affects patients’ occupational, social, and overall quality of life. We report a 41-year-old female presenting with persistent anxiety for the past three months. She experienced excessive worries about her health, children, financial problems, and work, accompanied by somatic symptoms such as shortness of breath, epigastric pain, tremors, and derealization. Mental status examination revealed a hypotymic mood, restricted affect, and excessive anxious thought content. Based on DSM-5 criteria, the patient was diagnosed with Generalized Anxiety Disorder (F41.1). The patient received combined pharmacotherapy (Sertraline 50 mg, Buspirone 10 mg, Diazepam 5 mg) and psychotherapy including Cognitive Behavioral Therapy (CBT), relaxation techniques, and psychoeducation. Management of GAD requires a multimodal approach. The combination of pharmacotherapy and psychotherapy provides superior outcomes compared to monotherapy, particularly in symptom reduction, functional improvement, and relapse prevention.